A relação entre oralidade e escrita em língua portuguesa no surdo - Andrade, Wagner Teobaldo Lopes de (2007)
The speaking-writing continuum is considered as an agent which determines and changes the language. The written language is important to the deaf communication because of their difficulty in developing the oral language. This research takes into account that written language is an important instrument to the deafs as members of society and a helpful way to register their ideas and thoughts. Considering that the students may be able to use written portuguese language at finishing basic school degree, this study aimed to investigate the occurrence of oral cues in the writing of the deaf in high school. Specifically, we aimed to characterize the discoursive markers, repetition and paraphrase occurring in oralized and non-oralized deaf people by comparing the results of written texts produced by these two groups and then with that of listeners. The sample of the research was composed by fifteen oralized deafs and fifteen non-oralized deafs with pre-lingual deafness on deep degree, and fifteen listeners. The three groups answered a question sheet with six questions in order to analize the oral marks in a quantitative and qualitative basis. The results were submitted to a statistical treatment by applying the T-student test. The results showed a major use of discoursive markers, especially of sequential function, by oralized deafs and listeners. A statistical significant difference between the average of quantity of discoursive markers used by non-oralized deafs and listeners was found. The repetition was used mainly by the oralized deafs. The whole form of repetition and its adjacent position on writing prevailed within the three groups. As for the function, the topical functioning continuity prevailed in the deafs and the comprehension function prevailed in the listeners. The occurence of paraphrase was small in the subjects writing and the nonoralized deafs had no occurence at all. To conclude, the orality marks were present in the deafs writing, suggesting the realization of the speaking/writing relation in these subjects, especially the oralized ones, as well as with the listeners. The major use of orality marks among the oralized deafs suggests the influence over text structure mainly related to textual cohesion. If we are to consider the use of orality marks as a factor of textual cohesion, these results can be the first step to optimize the deafs writing, mainly the non-oralized ones, in order to estimulate the cohesion on these subjects texts